Analisis Implementasi Pemidanaan Terhadap Admin Judi Online dalam Perspektif Hukum Pidana - Riyan Giri Aldiansyah; Boedi Prasetyo (Jurnal Hukum Lex Generalis, 2024)
Criminal punishment for online gambling administrators in Indonesia is a crucial aspect of law enforcement related to the growing issue of online gambling, which has developed alongside technological advancements. This article analyzes the legal foundations used to punish online gambling administrators, including Law No. 11 of 2008 on Information and Electronic Transactions (ITE), the Indonesian Criminal Code (KUHP), and Government Regulation No. 71 of 2019 on the Implementation of Electronic Transaction Systems. Online gambling administrators, as organizers and managers of gambling platforms, hold significant criminal responsibility, both for facilitating gambling activities and for disseminating information related to gambling. Criminal punishment is imposed on administrators based on their involvement in providing platforms for betting, managing transactions, and promoting gambling through digital media. Additionally, this article discusses the challenges in enforcing laws against online gambling administrators, such as the anonymity of perpetrators, unclear server locations, and limited resources for law enforcement. Several court cases related to the criminal punishment of online gambling administrators, such as Decision No. 852/Pid. Sus/2020/PN. Mdn and Decision No. 579/Pid. B/2023/PN SBY, are used as examples of how criminal law is applied in practice. Despite these significant challenges, consistent law enforcement and international collaboration are essential to reducing online gambling practices that harm both society and the country. It is hoped that by applying strict criminal sanctions, a deterrent effect will be achieved, limiting the spread of online gambling in Indonesia.